Challenges for the Preservation of the Malay Language in the Imminence of the Fourth Industrial Revolution - Graf, Arndt (Melayu: Jurnal Antarabangsa Dunia Melayu, 2020)
This article analyses the challenges in preserving the Malay language as we head into the Fourth Industrial Revolution. The discussion begins with the history of the concept of Industry 4.0, including the "Kondratiev waves", followed by a theoretical discussion about the relation between the major changes that will take place in technology, language, culture and politics. The emergence of Industry 4.0 has been promoted by the German government in response to their waning role in the global economy as a result of the rapid development of the Chinese economy, as well as that of other non-English-speaking or non-Anglosphere countries. The position of Malay and Bahasa Indonesia in Malaysia, Indonesia and Brunei is expected to remain an important one as long as the economic development of these three countries is maintained. The concept of Industry 4.0, that is, a combination of the "Internet of Things" with the "Internet of Services" provides much opportunity for users in Malaysia, Indonesia and Brunei to continue speaking Malay. The implications of this for the higher education system are to increase the employability of students in the era of Industry 4.0 in several ways, including: (1) enriching its scientific and technological terminology; (2) increasing the wealth of resources in Malay through publication of journal articles and books that suit the Industry 4.0 era; (3) teaching all subjects in colleges and universities in Malay. In other words, Malay it is imperative that Malay be made the language of Industry 4.0 discourse. Keywords: Malay, Fourth Industrial Revolution, Malaysia - Indonesia - Brunei Darussalam, implications for the system of Higher Education